Les techniques instrumentales de mesure de la force musculaire et de la balance musculaire : le point sur la technologie isocinétique - Cozette, M.; Leprêtre, P.-M.; Weissland, T. (Movement & Sport Sciences - Science & Motricité, 2021)
The strength balance between the agonist and antagonist muscles is a key parameter for motor skills and joint stability during movement. Dynamic joint stabilization is a fundamental concept in the areas of performance, prevention, and rehabilitation. Several techniques make it possible to quantify muscle strength according to the modality of muscle contraction. We distinguish isometric, inertial, and isokinetic assessments. Among these techniques, the isokinetic assessment seem to be the most relevant to quantify the agonist-antagonist muscle balance while considering the mechanical properties of the muscle. Nevertheless, the isokinetic technique has certain limits, particularly related to the exclusive use of the peak torque.